2019
DOI: 10.3390/nu11010098
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Supplementation, Pro-Resolving Mediators, and Clinical Outcomes in Maternal-Infant Pairs

Abstract: Omega (n)-3 fatty acids are vital to neonatal maturation, and recent investigations reveal n-3 fatty acids serve as substrates for the biosynthesis of specialized pro-resolving lipid mediators (SPM) that have anti-inflammatory and immune-stimulating effects. The role SPM play in the protection against negative maternal-fetal health outcomes is unclear, and there are no current biomarkers of n-3 fatty acid sufficiency. We sought to ascertain the relationships between n-3 fatty acid intake, SPM levels, and mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The identification that omega-3 fatty acids are metabolized into bioactive pro-inflammation resolution lipids, SPM [7], provides a potential link between the known benefits of omega-3 fatty acid supplementation in pregnancy and their conferred protection from negative inflammation-associated perinatal outcomes. Of note, we recently identified that maternal circulating blood collected at delivery has significantly higher levels of SPM RvD1 and RvD2 compared to cord blood, suggesting that the placenta could be a site of action for maternal SPM [16]. Through the investigations described herein, we have identified the placenta as a site of action for SPM, with key actions on specific placental cell types including placental vascular smooth muscle and EVT that could confer protection against inflammatory injury and disease.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The identification that omega-3 fatty acids are metabolized into bioactive pro-inflammation resolution lipids, SPM [7], provides a potential link between the known benefits of omega-3 fatty acid supplementation in pregnancy and their conferred protection from negative inflammation-associated perinatal outcomes. Of note, we recently identified that maternal circulating blood collected at delivery has significantly higher levels of SPM RvD1 and RvD2 compared to cord blood, suggesting that the placenta could be a site of action for maternal SPM [16]. Through the investigations described herein, we have identified the placenta as a site of action for SPM, with key actions on specific placental cell types including placental vascular smooth muscle and EVT that could confer protection against inflammatory injury and disease.…”
Section: Discussionmentioning
confidence: 77%
“…Also, a recent study identified that supplementation of omega-3 fatty acids during pregnancy increases precursors of SPM in newborns [19]. Adding to these studies are our recent findings that RvD1 and RvD2 levels were significantly elevated in maternal blood collected at labor as compared to cord blood, suggesting the placenta as a potential site of action for maternal circulating SPM [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many immune cell types produce SPMs [ 56 , 57 , 58 , 59 ]. SPMs have been measured in human plasma including from pregnant women [ 60 ], umbilical cord [ 60 , 61 , 62 ], infants [ 61 ] and children [ 61 , 62 ]. Human breast milk has been reported to contain SPMs [ 63 , 64 , 65 ].…”
Section: Long-chain Polyunsaturated Fatty Acids Lipid Mediators mentioning
confidence: 99%
“…Both aspirintriggered and non-aspirin-triggered SPM have biological activity (88)(89)(90) . A variety of SPM have been reported in human blood (91)(92)(93) , including umbilical cord blood (94,95) , adipose tissue (96) , breast milk (97) and synovial fluid (98) . Supplemental EPA and DHA has been shown to result in higher concentrations of some SPM in human blood (91)(92)(93)99) .…”
Section: N-3 Pufa Lipid Rafts Nfκb Activation and Inflammatory Cytomentioning
confidence: 99%